EKSTRAKSI ABU VULKANIK GUNUNG SINABUNG UNTUK MENGHASILKAN SILIKA GEL - Maulida; Melva Ginting; Herlinawati Wici (Talenta Publisher (Universitas Sumatera Utara), 2017)
Silica gel is one of the silica based material. This research aimed to utilizetion volcanic ash of Sinabung mountains to make silica gel by extraction method. Volcanic ash was extracted using NaOH 4M for 30, 60, 190 and 120 minutes. Gel was formed by addip HCl 4, 6,and 8M. Sample were analyzed of using FTIR, SEM-EDX, gravimetri and AAS. Analysis silica sodium solution with concentration variation showed the biggest silica was 120 minutes. FTIR result indicated the presence of Si in volcanic ash and siloxane (Si-O-Si). SEM-EDX result silica content of silica gel was 51.96%. XRD result showed that diameter of silica was 33.412 nm and the crystallinity was 89%. Silica was applied on the largest Cu (II) absorption rate was130.725 mg/g with an adsorption efficiency of 98.66%.